Digital innovation in islamic guidance: Fuzzy mamdani-based stress level detection for muslim adolescents - Amal, Muhammad Niltal; Handayani, Maya Rini (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2025)
Purpose - The purpose of this study is to address the urgent need for a reliable and accessible preliminary assessment tool for mental health issues among Indonesian adolescents, a demographic significantly impacted by recent societal changes and showing high rates of psychological distress (e.g., 34.9% experiencing mental problems per I-NAMHS 2022) Method - The methodology employed is the design and development of a web-based expert system utilizing Fuzzy Logic to diagnose stress symptoms. The system is structured with four core components (User Interface, Knowledge Base, Inference Mechanism, Working Memory) and incorporates Fuzzy Tsukamoto/Mamdani/Sugeno principles for mapping firm numerical symptom inputs to linguistic variables through Fuzzification and Defuzzification processes. Result - The result (anticipated/achieved) is a functional, dual-role web system (Admin/User) capable of providing objective, preliminary stress categorization, thereby serving as a first step toward early intervention. Implication – The implication of this work is twofold: clinically, it provides an immediate, non-expert-dependent tool for initial screening; ethically and religiously, it supports the collective obligation (fard kifayah) to safeguard youth mental well-being and maintain their fitrah. Originality/Value - The originality of this research lies in the specific integration of Fuzzy Logic reasoning within a web-based expert system tailored explicitly to the Indonesian adolescent context for stress awareness and preliminary diagnosis.*** Tujuan - Tujuan studi ini adalah untuk memenuhi kebutuhan mendesak akan alat penilaian awal yang andal dan mudah diakses untuk masalah kesehatan mental di kalangan remaja Indonesia, kelompok demografis yang sangat terdampak oleh perubahan sosial terkini dan menunjukkan tingkat gangguan psikologis yang tinggi (misalnya, 34,9% mengalami masalah mental menurut I-NAMHS 2022) Metode - Metode yang digunakan adalah desain dan pengembangan sistem pakar berbasis web yang memanfaatkan Logika Fuzzy untuk mendiagnosis gejala stres. Sistem ini terdiri dari empat komponen inti (Antarmuka Pengguna, Basis Pengetahuan, Mekanisme Inferensi, Memori Kerja) dan mengintegrasikan prinsip-prinsip Fuzzy Tsukamoto/Mamdani/Sugeno untuk memetakan masukan numerik gejala yang pasti ke variabel linguistik melalui proses Fuzzifikasi dan Defuzzifikasi. Hasil - Hasil (diperkirakan/tercapai) adalah sistem web fungsional dengan dua peran (Admin/Pengguna) yang mampu memberikan kategorisasi stres awal yang objektif, sehingga berfungsi sebagai langkah awal menuju intervensi dini. Implikasi – Implikasi dari penelitian ini dua arah: secara klinis, menyediakan alat skrining awal yang segera dan tidak bergantung pada ahli; secara etis dan agama, mendukung kewajiban kolektif (fard kifayah) untuk melindungi kesejahteraan mental remaja dan menjaga fitrah mereka. Orisinalitas/Nilai - Keaslian penelitian ini terletak pada integrasi spesifik logika fuzzy dalam sistem pakar berbasis web yang dirancang khusus untuk konteks remaja Indonesia dalam kesadaran stres dan diagnosis awal.